Sustainable consumption and the Global South: A conceptual exposition - Bhar, Soumyajit (Frontiers in Sustainability, 2023)
Although deliberations around the idea of sustainable consumption have triggered pro-environmental consumption behaviors, empirical works show such consumption choices hardly manage to lower the overall environmental impacts of their total consumption baskets. Driven by corporate-led globalization, most developing countries have adopted the prevailing neoliberal economic model centered on growthism and developmentalism. What complicates the situation further is that this capitalistic economic model fetishizes the wealthy and valorizes aspirations that shape socio-culturally held notions of good life towards overconsumption, especially in the Global South. The discussion on sustainable consumption needs to expand its scope from the post-materialistic discourses in the Global North to realign itself with the developmental discourse in the GS. Expanding this scope is easier said than done because of the fundamental dependency of the neo-liberal economic policy-driven developmentalism on consumerism. Once these macro-economic priorities percolate into socio-cultural priorities, further driving individuals’ sense of the good life, it becomes even more challenging to decouple materialistically-oriented need-satisfiers from wellbeing. Therefore, it is to theorize how the act of consumption happens at the complex intersections of political-economic priorities, socio-cultural conventions, and individual aspirations for a better life, which is even more so relevant in the context of the GS. It is critical to understand, especially for the Global South, how these structural factors percolate into socio-cultural and individual priorities through the changing notions of the good life and eventually act as the fundamental sustaining factors that keep the prevailing political-economic arrangements running.